ANALISIS ATAS ADANYA PRAKTEK NOTARIS YANG DITETAPKAN SEBAGAI PELANGGARAN HUKUM DI POLRESTA MEDAN - LEOVIN GINHO (PREMISE LAW JURNAL, 2017)
The profession of a Notary as reliable position has lately become public attention because there many Notaries undergo the process of summoning by the Police with the charging of violation against the certificates they have made. There are different status of summon by the Police, either as witnesses or as the suspected. As a public official and a professional, a Notary has an important profession in creating legal certainty for the people. He is the preventive domain upon the legal problem through authentic deeds he has made as complete evidence in the Court. It cannot be imagined if a Notary himself becomes the source of legal problem because the credibility of the deeds he has made is suspected by the people. As a prestigious, honorable, noble, and worthy professional, a Notary has the responsibility to maintain his position by presenting good and honorable behavior and attitude.Keywords: Notary, Violation of Law, Code of Ethics